Transparent Celadon with Phase-Separated Structure: Study on the Technological Characteristics and Coloring Mechanism of Celadons from the Lieshan Kiln - Qijiang Li; Jingyun Wang; Chao Chen; Tao Fang; Chenyi Gao; Jinwei Li (Crystals)
The excavation of the Lieshan Kiln site represents a significant advance in the field of ceramic archaeology. Previous scholars fixated on the white porcelain unearthed from this kiln, yet this study zeroed in on celadon from the Northern Song and Jin Dynasties. Celadon samples were analyzed using colorimetry, energy-dispersive X-ray fluorescence spectroscopy (ED-XRF), scanning electron microscopy (SEM), polarizing microscopy, X-ray photoelectron spectroscopy (XPS), and thermal expansion analysis. Results revealed that material and technological advancements in the production of the Lieshan Kiln and reveal the special phase-separated structure in the glaze of the transparent celadon, with a weakly reduced firing atmosphere. Celadon bodies from both periods were crafted from local sedimentary clays in a single-ingredient formula, with the Jin Dynasty refining the preparation, leading to enhanced density and higher firing temperatures compared to the Northern Song Dynasty. The celadon glaze, a high-calcium type made up of glaze ash and specific clays, differed from the body materials. The high SiO2/Al2O3 molar ratio, along with Fe2O3 and trace P2O5, promoted phase separation. Glaze coloration was modulated by the interaction of Fe3+ and Fe2+ ions, and chemical coloration by Fe ions prevailed when phase-separated particles were minute enough to avoid Rayleigh or Mie scattering. In conclusion, the study deepens the understanding of ancient ceramic production by exploring the phase separation structure and coloring mechanism of the celadon.